Peran Wakaf Sumur Dalam Meningkatkan Kesejahteraan Masyarakat Pamekasan (Studi Kasus Program Yayasan Cahaya Ummat) - Nawwaf Nawwaf; Kholid Saifulloh (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the role of wells waqf in improving people's welfare in a program developed by the Cahaya Ummat Foundation. The type of research used is qualitative research. The data collection techniques were interviews, documentation, and observation at the Cahaya Ummat Foundation. The results of this study indicate that the community has been assisted by the Air Madura alms program developed by the Cahaya Ummat Foundation; the construction of waqf wells which was carried out at 60 locations, resulted in convenience for the community to meet their needs for clean water and made it easier for the community to carry out activities. The community has experienced an increase in welfare and the economy. This can be noticed in the Wells Waqf program so that various businesses carried out by the surrounding community can run well, especially in the agricultural and livestock sectors.